Co-contraction of the core muscles during Pilates exercise on the Wunda Chair - Panhan, Ana Carolina (2020)
BACKGROUND: The co-contraction of the core muscles has been reported as the key mechanism towards spinal stability. Classic Pilates exercises aimed at these muscles are known to improve the stability and strength of the trunk without damaging the deep structures of the spine. OBJECTIVE: To evaluate the co-contraction of the mobilizing (rectus abdominis; longissimus) and stabilizing (multifidus; internal oblique) trunk muscles during Pilates exercises - going up front, mountain climber, and swan. METHODS: Sixteen women, all Pilates practitioners, participated in the study. The stabilizing and mobilizing muscles of the trunk (right side) were submitted to electromyography to calculate the percentage of co-contraction during the exercises. One-way repeated measures analysis of variance (ANOVA) was used to verify the difference in %COCON between stabilizers and mobilizers among the three exercises. The post-hoc Bonferroni test (P< 0.01) was applied when necessary. The paired t-test (P< 0.01) was used to verify the difference in %COCON between stabilizers and mobilizers separately for each exercise. RESULTS: The co-contraction values of the stabilizers were higher than those of the mobilizers for all exercises. The going up front (stabilizers) and the swan (mobilizers) exercises showed the highest %COCON values. CONCLUSIONS: The Pilates method is effective for either rehabilitating pathologies or training the trunk muscles in healthy individuals and athletes.